Niemandsland. - Blake, William; Goldstein, Zvi; Gonzalez-Foerster, Dominique; Graham, Rodney; Heynen, Julian; Matheson, Richard; Richter, Gerhard; Warhol, Andy; de Cordier, Thierry; Museum Haus Lange, Krefeld; Museum Haus Esters, Krefeld; Kunstmuseen der Stadt Krefeld (Krefeld : Museum Haus Lange, 1997)
Balka, Miroslaw ; de Cordier, Thierry ; Eichhorn, Maria ; Goldstein, Zvi ; Gonzalez-Foerster, Dominique ; Graham, Rodney ; Christine, Käthe Seidel - ; Hohenbüchler, Irene ; Stengel, Eberhard ; Huws, Bethan ; Scanlan, Joe ; Schneider, Gregor ; Slominski, Andreas
biografie
Niemandsland, Haus Lange und Haus Esters, Krefeld, 8.6. - 17.8.1997
Duits & Engels & Frans
boek